2008
DOI: 10.1007/s11468-008-9074-y
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals Forces Between Plasmonic Nanoparticles

Abstract: We propose a new approach to calculate van der Waals forces between nanoparticles where the van der Waals energy can be reduced to the energy of localized plasmons in nanoparticles. The general theory is applied to describe the interaction between two metallic nanoparticles and between a nanoparticle and a perfectly conducting plane. Our results could be used to prove experimentally the existence of new, recently predicted type of plasmon oscillation (Klimov and Guzatov, Phys Rev B 75:024303, 2007a; Klimov a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Approximations have been suggested in the limit of high azimuthal number m based on the bi-spherical scheme [15]; it has been shown that these modes are important when calculating the van der Waals attraction between spheres [37,52]. It would be interesting to consider limits where either or both n and m are large using singular perturbation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Approximations have been suggested in the limit of high azimuthal number m based on the bi-spherical scheme [15]; it has been shown that these modes are important when calculating the van der Waals attraction between spheres [37,52]. It would be interesting to consider limits where either or both n and m are large using singular perturbation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…±2 V. The observed change in the microstructure is assumed to be the reason for the significant decrease in the sample resistance after applying a high enough voltage. An increased mobility of the particles after exceeding T g can induce secondary agglomeration of the particles driven by the dispersion forces [18] and the applied electric field, which enhances the attraction of the particles towards each other and aligns them into chains [19]. Dipole moments induced in the particles by an external electric field significantly enhance attractive interparticle forces along the chains.…”
Section: Resultsmentioning
confidence: 99%
“…It is also very important that one can strictly prove that any eigensolution of (1) satisfies the condition of full loss compensation, that is: (7) where G L V , V are the volumes of gain and lossy nanoparticles. Thereby if one attributes effective permittivity [27] to the whole system, its imaginary part will be equal to zero, so our system is similar to pseudo-Hermitian systems [28].…”
Section: Materials Independent Eigenvalues and Eigenmodesmentioning
confidence: 99%
“…In dimers, i.e. systems consisting of two particles, in the case of small losses and small distances between the particles, an essentially new type of localized oscillations ("plasmonic molecules") can be seen [5][6][7].…”
Section: Introductionmentioning
confidence: 99%